Diagnostic Accuracy of Quantitative Washout Calculated on Triphasic CT Scan for Diagnosis of Hepatocellular Carcinoma keeping Histopathology as Gold Standard - MARYAM SAMAD; SARA NISAR; SAMIA ABBAS; MUDASSIR MALIK; KHAWAR SHAHZAD; MUHAMMAD HASEEB MALIK (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find out how accurate the quantitative washout is at diagnosing hepatocellular carcinoma on a triphasic CT scan compared to the histopathology, which is the gold standard. It can be used as a supplement to the subjective visual analysis of washout to help the radiologist diagnose hepatocellular carcinoma. Methods: From the OPD and indoor database, 150 patients of both sexes were included who had abnormal lesions confirmed by ultrasound. In order to quantify washout during the delayed phase, CT scans were performed in three phases on all patients. On delayed phase, a region of interest between normal liver parenchyma and lesions was obtained. Those lesions having a percent attenuation ratio greater than 107 were identified as hepatocellular carcinoma. Results: The ages of 150 patients who met the inclusion criteria ranged from 15 to 85. There were 93(62%) males and 57(38%) females, for a total gender ratio of 2:1. Of the 105 patients who tested positive for HCC on a CT scan, 96 actually had HCC. Among 45 patients who tested negative for HCC on a triphasic CT scan, 8 were erroneously labelled as negative. Quantitative washout on Triphasic CT scan has an overall sensitivity of 92.30%, a specificity of 80.40%, a positive predictive value of 82.20%, a negative predictive value of 88.66% and a diagnostic accuracy of 88.66% for identifying hepatocellular cancer. Conclusion: Based on our findings, quantitative washout assessment for hepatocellular carcinoma is an easy, highly sensitive, and objective way that can be used as an adjunct to qualitative washout for hepatocellular carcinoma diagnosis. Keywords: Hepatocellular carcinoma HCC, Percentage attenuation ratio, Washout, Delayed phase